Assessment of Left Ventricular Systolic Function by Cardiovascular Magnetic Resonance Compressed Sensing Real-Time Cine Imaging Combined With Area-Length Method in Normal Sinus Rhythm and Atrial Fibrillation - Yin, Gang; Cui, Chen; An, Jing; Zhao, Kankan; Yang, Kai; Li, Shuang; Yang, Xinling; Wang, Jiaxin; Dong, Zhixiang; Yu, Shiqin; He, Jian; Chen, Xiuyu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The most-commonly used multi-slice Simpson’s method employed with routine two-dimensional segmented cine images makes it difficult to evaluate left ventricular (LV) volume and function due to endocardial border blurring and beat-to-beat variation during atrial fibrillation (AF) status. Objectives: To assess the feasibility of compressed sensing real-time (CSRT) cine imaging combined with an area-length method for quantification of LV systolic function in normal sinus rhythm (NSR) and AF. Methods: The CSRT cine sequence and routine segmented balanced Steady-State-Free-Precession cine sequence were performed in 71 patients with NSR (n=36) or AF (n=35). Image quality and edge sharpness for both sequences were assessed. The LV functional measurements in patients with NSR included end-diastolic volume (EDV), end-systolic volume (ESV), stroke volume (SV), ejection fraction (EF), cardiac output (CO), cardiac index (CI), and LV mass (LVM); all were assessed using segmented cine with Simpson’s rule in short axis (SegSA_Simpson, as a reference standard) and area-length (AL) method in the two chamber (Seg2CH_AL) or four chamber (Seg4CH_AL) and CSRT cine with AL method in the two chamber (CSRT2CH_AL) or four chamber (CSRT4CH_AL). Finally, the mean, maximum, and minimum values of each LV functional parameter (EDV/ESV/SV/EF/CO/CI/LVM/heart rate (HR)) from 4 5 consecutive heartbeats were measured using CSRT2CH_AL in patients with AF. Results: In patients with NSR, measurements of EDV (p >0.05), ESV (p >0.05), SV (p >0.05), EF (p >0.05), and LVM (p >0.05) assessed with CSRT2CH_AL did not differ significantly from those obtained with SegSA_Simpson. In patients with AF, CSRT image quality score (p <0.001) and edge sharpness (p<0.001) both were significantly higher than those obtained from segmented cine. The CSRT2CH_AL provided significantly different results among mean, maximum, and minimum values of each LV parameter from 4 5 consecutive heartbeats (all p <0.001) with strong inter- and intra-observer agreement in AF. Conclusions: The CSRT cine sequence combined with two chamber area-length analysis accurately assessed LV systolic function in NSR. This approach is expected to permit the assessment of multiple parameters in consecutive heartbeats with good inter- and intra-observer reproducibility for beat-to-beat analysis of LV function in AF.